Reduction in thermal plasticity of life history traits in response to cold selection: an experimental evolution study using Drosophila melanogaster - Roy, Rishav; Chattopadhyay, Aradhya; Deb Sharma, Sreebes; Mondal, Aharna; Biswas, Payel; Ghosh, Shampa M. (Frontiers in Ecology and Evolution, 2025)
IntroductionHow selection influences phenotypic plasticity is an important question in evolutionary biology. We report an experimental evolution study that examined how prolonged selection at cold vs. warm temperature impacts the thermal plasticity of traits like reproductive output, body size, and body water content in Drosophila melanogaster.MethodsWe conducted the study on two sets of large, outbred fly populations: one maintained at the standard fly rearing temperature, i.e., 25°C, and another selected at cold temperature, i.e., 17°C, for 3.5 years. Both selection lines were derived from the same ancestral population.Results and discussionWe found that while 25°C selected females lay significantly fewer eggs in cold compared to warm or optimal rearing temperature of 25°C, the 17°C selected females have consistent or canalized fecundity levels across warm and cold conditions. Sustained fecundity levels across cold and warm conditions are potential marks of adaptation to a broader thermal range. While phenotypic plasticity may aid in adaptation to new environments, for traits such as fecundity, consistent levels across environments, that is, low plasticity, may be more adaptive. We also found that male flies from cold vs. warm selection regimes differ in their thermal plasticity. Plasticity of dry weight and body water content was reduced in the cold-selected males, indicating the evolution of canalized levels for these traits too. While canalized fecundity levels across temperatures can potentially help in thermal adaptation, the significance of reduced plasticity of male body size and water content needs to be investigated in the future.